Isolation and identification of fungal from bread produced in some Calabar bakeries - Uche, Onyinyechi Faithful (My University, 2025)
Bread is a staple food in the developed and developing world it is widely accepted and consumed by people of all ages and nationalities, including Nigeria. Bread is a staple food that can be susceptible to microbial spoilage due to mold growth and fungi. The so aim is to determine the identification and isolation of fungi from bread produce in some Calabar Bakeries. The results reveal the presence of four fungi species., Rhizophus sp (21%), Penicillium sp (25%), Aspergillus sp (31%), Mucor sp (23%) the number of isolates varies across samples with Aspergillus sp and Penicillium sp showing the highest level of contamination respectively 31% and 25%, while Mucor sp and Rhizopus sp has the lowest count with are 23% and 21%. The observed fungi contamination suggests four hygiene practices during production and post production, as well as suboptimal storage conditions. The study findings review that bread samples distributed in some Calabar bakeries in cross rivers state exhibited contaminations with a diverse array of bacterial and fungal species, this contamination poses a significant safety risks to human health, take potentially exposing the population food borne diseases
Keywords: Isolation; Bread; Fungal; Penicillium sp; Rhizophus sp; Aspergillus sp; Mucor sp; Shelf-life; mold; Bakeries